Preformulation of a liquid dosage formulation of captopril for pediatric use: drug-excipient compatibility and stability studies - Janaina da Silva Goes; Fátima Duarte Freire; Túlio Flávio Accioly de Lima e Moura; Cícero Flávio Soares Aragão; Fernanda Nervo Raffin (Universidade de São Paulo, 2019)
Currently, medications used in children are typically modified from pharmaceutical dosage forms designed for adults. Captopril is widely adapted to liquid formulations for use in hospitals. Its stability in the aqueous medium is reduced since it undergoes oxidation producing captopril disulfide (its main metabolite). The aim of this formulation study was to suggest favorable conditions for the development of a stable captopril formulation. The compatibility between the drug and excipients was evaluated by differential scanning calorimetry analysis (DSC). For studies in solution, different formulations were prepared according to a factorial design varying EDTA concentration, water purity and pH. The resultant formulations were stored at 60°C and analyzed over a twelve-day period using HPLC. The DSC curves obtained suggested, although not conclusive to elucidation, interactions of captopril with citric acid and sucralose. The stability study of these solutions revealed that the variables significantly influenced captopril content, which degraded at zero order kinetics and rates differing by a factor of up to 7 times, where pH proved the most influential factor. Interactions between variables were observed. Therefore, development of a stable captopril formulation is feasible provided EDTA and a buffering agent is used at suitable concentrations (0.08% and pH 3.85).